2008
DOI: 10.1080/00222340802403420
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal Crystallization Kinetics and Microhardness of PP/CNT Composites

Abstract: The nonisothermal crystallization kinetics and microhardness of nanocomposites consisting of a polypropylene matrix (PP) and carbon nanotube filler (CNT) have been investigated. Three types of PP matrixes have been used: two of them are nonfunctionalized PP that differ slightly in their melt flow index, whereas the third is grafted with maleic anhydride (MA). Ozawa formalism has been used to study the nonisothermal crystallization kinetics. The results show that the CNT filler has a nucleation role in the noni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The crystallization temperature of PP, from the melt, increased approximately 20 • C above that of pure PP, using a concentration as low as 0.05 wt% of carbon nanoparticles. This excellent nucleating capacity of CNTs and CNFs has also been reported by other authors [9][10][11][12][13], though some authors have found that above 4 wt% this ability reaches a plateau and remains constant [14]. In addition to this nucleating effect, it has been found, via TGA, that these carbon nanoparticles increase the temperature for the onset of the PP decomposition [12,13,[15][16][17] by as much as 20 • C [18].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The crystallization temperature of PP, from the melt, increased approximately 20 • C above that of pure PP, using a concentration as low as 0.05 wt% of carbon nanoparticles. This excellent nucleating capacity of CNTs and CNFs has also been reported by other authors [9][10][11][12][13], though some authors have found that above 4 wt% this ability reaches a plateau and remains constant [14]. In addition to this nucleating effect, it has been found, via TGA, that these carbon nanoparticles increase the temperature for the onset of the PP decomposition [12,13,[15][16][17] by as much as 20 • C [18].…”
Section: Introductionsupporting
confidence: 82%
“…A series of PP compositions with 0.05 wt% of each of CNFs, CNTs, and LiBe were prepared via melt mixing for 10 min, at 170 • C and 50 rpm, in a Brabender torque rheometer mixing chamber. Very low nucleating agent concentrations (0.05 wt%) were in order to prevent the excess of nucleating particles from interfering with the spherulitic growth, as has been observed by other authors when using high CNTs or CNFs concentrations [9,14,19]. Plain PP was also passed through the mixer to produce blank samples.…”
Section: Sample Preparationmentioning
confidence: 99%
“…CNTs cause also a serious effect on the crystallization rate of PP and this can affect most of its properties. For this reason a lot of researchers have studied extensively the effect of CNTs on PP crystallinity [ 30 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. iPP has normally a slow crystallization rate, forming large spherulites.…”
Section: Pp/cnts Nanocompositesmentioning
confidence: 99%
“…It is also found that the sizes of spherulites and nucleation density of iPP/CNTs shows no obvious changes with increasing CNTs concentration from 0.2 wt % to 1.0 wt %, which infers that the nucleating effect of CNTs may saturate at least at CNTs concentration of 0.2 wt %. This implies that a further elevation of CNTs concentration does not further improve the nucleation effect [ 52 , 57 ].…”
Section: Pp/cnts Nanocompositesmentioning
confidence: 99%
“…Despite the large number of available articles referred to iPP/CNT systems, [7][8][9][10][11][12] the influence of the addition of CNT on the physical properties of sPP matrix is not so well studied. In this article, the morphological and thermal properties of sPP/multiwalled carbon nanotubes (MWCNT) nanocomposites are investigated by employing various techniques (scanning electron microscopy, X-ray diffraction, Raman spectroscopy, differential scanning calorimetry).…”
Section: Introductionmentioning
confidence: 99%